Spacing, Feedback, and Testing Boost Vocabulary Learning in a Web Application - Belardi, Angelo; Pedrett, Salome; Rothen, Nicolas; Reber, Thomas P. (Frontiers in Psychology, 2021)
Information and communication technology (ICT) becomes more prevalent in education its efficacy in general and that of specific learning applications in particular has not been fully established yet. One way to further improve learning applications could be to use insights from fundamental memory research. We here assess whether four established learning principles (spacing, feedback, testing, and multimodality) can be translated into an applied ICT context to facilitate vocabulary learning in a self-developed web application. Effects on the amount of newly learned vocabulary were assessed in a mixed factorial design (3×2×2×2) with the independent variables Spacing (between-subjects; one, two, or four sessions), Feedback (within-subjects; with or without), Testing (within-subjects, 70% or 30% retrieval trials), and Multimodality (within-subjects; unimodal or multimodal). Data from 79 participants was analyzed and revealed significant main effects for Spacing (F[2, 76] = 8.51, p = 0.0005, partial eta^2= 0.18) and Feedback (F[1, 76] = 21.38, p<0.001, partial eta^2= 0.22), and a significant interaction between Feedback and Testing (F[1, 76] = 14.12, p = 0.0003, partial eta^2= 0.16). Optimal Spacing and the presence of corrective Feedback in combination with Testing together boost learning by 29% as compared to non-optimal realizations (massed learning, testing with lack of corrective feedback). Our findings indicate that established learning principles derived from basic memory research can successfully be implemented in web applications to optimize vocabulary learning.